Pengaruh Ukuran Bank, Manajemen Aset Perusahaan, Kapitalisasi Pasar danProfitabilitas terhadap Kredit Bermasalah pada Bank yang terdaftar di BEI - Pramudita, Aditya; Subekti, Imam (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aimed to examine the effect of bank size, asset management companies, market capitalization and profitability of the non-performing loans. The population used in this study is a commercial bank listed on the Indonesia Stock Exchange in the period 2008-2012. The samples in this study were taken by using the method of data collection is called purposive sampling method. The analysis technique used is multiple linear regression. The research is based on the phenomenon of non-performing loans in Indonesia. Non-performing loans due to a delay or return of funds already disbursed. Funds derived from the total assets showed that not all categories of assets that may affect the non-performing loans. The test results showed that the variable asset management company and affect the profitability of non-performing loans. Since both of these variables explain the liquidity of funds, the composition of funds and fund management method that could lead to a non-performing loans. But the results of this test showed that the variable bank size and market capitalization has no effect on non-performing loans. Due to the variable bank sizeexpressed in total assets that are the source of wealth owned by the bank and not all can be categorized as liquid funds. While the market capitalization variable is the change in the price of shares traded on the stock market is not how much the distribution of funds. Keywords: bank size, asset management companies, market capitalization, profitability, non-performing loans